Pengaruh Eksistensi Saham, Indikator Pasar, dan Rasio Keuangan Terhadap Profitabilitas - Bibi Faiza Farhana; Clarashinta Canggih (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
High profitability is a primary goal for many companies, especially those that have conducted an initial public offering (IPO) and are listed on a stock index. This study aims to analyze whether stock presence, trading volume, market capitalization, liquidity, solvency, and working capital management influence the profitability of companies that enter and exit the Jakarta Islamic Index (JII). The study uses quarterly data from 2022 to 2024, covering 20 companies that have experienced more than one entry or exit from the index. Stock price movements occur every six months following index evaluations conducted by the Indonesia Stock Exchange (IDX). The findings reveal that stock presence, trading volume, liquidity, and one component of working capital management, namely Days Payable Outstanding (DPO), have a significant impact on company profitability. On the other hand, market capitalization, solvency, and two other components of working capital management, Days Sales Outstanding (DSO) and Days Inventory Outstanding (DIO), do not significantly affect profitability.